Meta-analysis of a mindfulness yoga exercise intervention on depression – based on intervention studies in China - Yang, Yuehang; Cao, Dawei; Lyu, Teng; Gao, Wei (Frontiers in Psychology, 2023)
Background Using statistical methods to analyze and summarize the research data of the inclusion criteria, to provide a quantitative average effect size to interpret the influence of mindfulness yoga exercise on patients with different depressive symptoms, explain the therapeutic effect of mindfulness yoga therapy on depression and its possible mechanism of action, and provide new ideas for the clinical treatment of patients with depression. Method Review Manage 5.4 software was used to comprehensively evaluate the effect of yoga exercise on depression interventions to provide a reference for improving mental health. CNKI, PubMed, Web of science, EBSCO were searched for all case–control research articles on yoga for depression from 2000 to 2022. After screening, data extraction and quality evaluation of randomized controlled trials (RCTs) by inclusion and exclusion criteria, a total of 22 studies with 2,216 patients were included, including 1,101 in the yoga intervention group and 1,115 in the control group. Results The results showed a large heterogeneity in the literature on the effect of yoga exercise on depression, with a combined total effect size [SMD = −1.53, 95%CI (−1.96, −1.10), p < 0.00001]. Conclusion Mindfulness yoga exercise is effective in preventing and treating depression and improving mental health, and may be considered as a non-medical, low-cost intervention as an adjunct to pharmacological treatment.